Apuntes sobre la condición metafórica en el habla coloquial costarricense - Rosa Aguilar, Alma (2010)
This study aims to explore metaphor in Costa Rican colloquial language which was present in the social imaginary during the 20th century. It contains a metaphor’s inventory and proposes an attempt of classification and analysis focusing semantic and discursive aspects. The main purpose is rescuing this kind of intangible cultural Costa Rican patrimony.